Organizational structure of the notary office and principles of its structure - Solotskyi, D. O. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article is devoted to the study of the organizational structure of the notary public and the principles of its construction. In this context, it is noted that the organizational structure of the notary public reflects the competence and system of notarial bodies and officials authorized to carry out notarial activities. It is established that the organizational system of the notary public, depending on the legal status of its subjects and the presence of their powers regarding notarial activities, includes: 1) general subjects who can perform any notarial actions - a) notaries, who can be both state and private; b) authorized officials involved in notarial activities due to a territorial feature (those located outside the territory of Ukraine or in the territory of rural settlements); 2) special subjects who can perform certain notarial actions in cases specified by law - authorized officials involved in notarial activities due to a local feature. Attention is focused on the fact that the organizational system for building a notary public is based, first of all, on the principles of comprehensiveness and territorial-local accessibility. The impact of these principles on the activities of all entities that carry out notarial activities in full or perform individual notarial actions, regardless of their stay in the territory of Ukraine or outside it, is analyzed. It is noted that the introduction of the martial law legal regime in Ukraine mediated the need for mandatory consideration of the legislation on sanctions, which is manifested in the implementation of additional control during the acceptance of documents by diplomatic and consular institutions regarding the status of persons who have applied and their compliance with the legislation on the legal regime of martial law. The derived principles of the organization of notarial services are identified, namely: the performance of notarial acts and actions equivalent to them only by authorized persons; the possibility of appealing against the performed notarial acts or refusal to perform them; the obligation to be subordinate to the Ministry of Justice of Ukraine regardless of the position of the official performing the notarial act or the action equivalent to it in the notarial system or the place of performance of the notarial act; the obligation to register notarial acts and actions equivalent to them regardless of the position of the official performing the notarial act in the notarial system or the place of performance of the notarial act, etc.